Development of a Physics Instruction Model Based-on STEM Education Approach to Enhance Physics Learning Achievement, Critical Thinking, and Adversary Quotient of Upper Secondary Students - พิทักษ์, พิทธพนธ์; จินดานุรักษ์, ทวีศักดิ์; พินสุวรรณ์, ดวงเดือน; บุญประกอบ, มนัส (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2019)
This research was a research and development. The aim of this research were (1) to develop Physics Instruction Model Based-on STEM Education Approach to Enhance Physics Learning Achievement, Critical Thinking, and Adversary Quotient of Upper Secondary Students (2) to evaluate the effectiveness of the developed instructional model. The research procedure was divided into two phases. The first phase was the development of the instructional model that proceed in the following as: (1) the study of the concept and relevant literature to define the rationale of the constructional model, the objectives of the instructional model, the learning process, and the evaluation. (2) Examine the quality of the teaching model by expert evaluation. (3) Experiment with the instruction model by the pilot study. The sample consisted of 31 students in Mathayom Suksa 4/1 of Kraburiwittaya School in the second semester of the academic year 2016. The lesson plans based on the developed instruction model was used in this study. The results of the pilot study for improving the instruction model. The second phase was the evaluation of the developed instructional model by field try-out. The samples were 80 students in Mathayom Suksa IV of Kraburiwittaya school in the first semester of the academic year 2017, from cluster random sampling. The experimental design was the randomized pretest-posttest control group design. The instruments used in the study included (1) The Physics Achievement test with the reliability of 0.92. (2) The Critical Thinking test with the reliability of 0.98. and (3) The adversity Quotient Test by Kannika Suksamai (2006) with the reliability of 0.89. The data was analyzed by Multivariate Analysis of Variance (MANOVA) The findings were as follows: 1) Physics Instruction Model Based-on STEM Education Approach to Enhance Physics Learning Achievement, Critical Thinking, and Adversary Quotient of Upper Secondary Students consisted of four components; (1.1) rationale of the constructional model (1.2) the objectives of the instructional model (1.3) learning process which comprised two steps. They were (3.1) problematic situation design which is creating a problem situation using the P-T-PM-E format and (3.2) the step of the learning process has consisted of 6 steps: Step 1 Identifying the problem, Step 2 Investigation, Step 3 Generating possible solutions, Step 4 Decision making, Step 5 Producing the product, Step 6 Performance assessment, and (1.4) evaluation 2) Physics learning achievement, critical thinking ability and adversary quotient of the students who were taught by the developed instructional model was significantly higher than of the students who were taught by the traditional teaching model.